KREATIVITAS GURU DALAM MEMBUAT MEDIA PADA PEMBELAJARAN TEMATIK KELAS III DI MIS ROUDHOTUL ULUM PARIT SETIA KECAMATAN JAWAI TAHUN PELAJARAN 2023-2024 - Nurharani Nurharani; Rusiadi; H. Syaifuddin (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine Teachers' Creativity in Making Thematic Learning Media for grade III MIS Roudhotul Ulum Parit Setia, Jawai District, Academic Year 2023-2024. This research uses a qualitative approach and a qualitative descriptive type of research. Data collection techniques use interviews, observations and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study show that: 1) How teachers make media in Grade III thematic learning MIS Roudhotul Ulum Parit Setia Academic Year 2023-2024, Determining learning objectives, Analyzing learning materials, Paying attention to students' needs and interests, Using various sources such as images, videos, etc. 2) The problems faced by teachers in creating thematic learning media for Class III MIS Roudhotul Ulum Parit Setia for the 2023-2024 Academic Year are as follows: Limited time, Limited resources such as technological devices, Limited school budget. The way teachers evaluate the application of media in thematic learning for Class III MIS Roudhotul Ulum Parit Setia for the 2023-2024 Academic Year is as follows: Adjusted to the type of learning, education level, and needs of students, Evaluation method: Direct observation of student involvement and response, Test before and after media use to see the impact on understanding.